The Effect of Dietary Fiber Intake on Blood Glucose Levels Among Patients with Diabetes Mellitus at Jagir Primary Health Center, Surabaya, Indonesia - Yohanes Lodo Kaho; Maria Gonzalez (Lembaga Publikasi Ilmiah Nusantara, 2026)
Diabetes mellitus remains a major public health problem worldwide, particularly in developing countries, including Indonesia. Dietary fiber intake has been widely reported to play an important role in glycemic control among patients with diabetes mellitus. However, evidence at the primary healthcare level in Indonesia remains limited. This study aimed to analyze the effect of dietary fiber intake on blood glucose levels among patients with diabetes mellitus at Jagir Primary Health Center, Surabaya, Indonesia. A cross-sectional analytical study was conducted involving adult patients with type 2 diabetes mellitus. Dietary fiber intake was assessed using a semi-quantitative food frequency questionnaire, while blood glucose levels were obtained from medical records. Data were analyzed using correlation and multivariate regression tests. The results showed that patients with low dietary fiber intake tended to have significantly higher fasting and postprandial blood glucose levels compared to those with adequate fiber intake. These findings are consistent with previous studies reporting a negative association between fiber intake and blood glucose levels. In conclusion, adequate dietary fiber intake is associated with better glycemic control among patients with diabetes mellitus at the primary healthcare level. Strengthening nutrition education focusing on fiber-rich diets is strongly recommended.